2018
DOI: 10.1088/1758-5090/aaec22
|View full text |Cite
|
Sign up to set email alerts
|

Porous tissue strands: avascular building blocks for scalable tissue fabrication

Abstract: The scalability of cell aggregates such as spheroids, strands, and rings has been restricted by diffusion of nutrient and oxygen into their core. In this study, we introduce a novel concept in generating tissue building blocks with micropores, which represents an alternative solution for vascularization. Sodium alginate porogens were mixed with human adipose-derived stem cells, and loaded into tubular alginate capsules, followed by de-crosslinking of the capsules. The resultant cellular structure exhibited a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 77 publications
1
31
0
Order By: Relevance
“…It should be noted the used diameter of TSs is satisfactory to maintain the viability of chondrocytes because of their anaerobic nature. [22] Cellular alignment at different depth of TSs demonstrated that cells within ≈50 µm distance from edges were highly oriented along the longitudinal direction of TSs (Figure 4e). At the boundaries of TSs, cell movement subjected to the wall of alginate capsules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted the used diameter of TSs is satisfactory to maintain the viability of chondrocytes because of their anaerobic nature. [22] Cellular alignment at different depth of TSs demonstrated that cells within ≈50 µm distance from edges were highly oriented along the longitudinal direction of TSs (Figure 4e). At the boundaries of TSs, cell movement subjected to the wall of alginate capsules.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that 3D culture (e.g., hydrogel encapsulation and tissue spheroid) induced more reliable chondrogenic differentiation of stem cells than conventional monolayer culture, [32][33][34] TSs in Group 2 exhibited lower chondrogenic functionality, which might be due to their thick nature, limiting the diffusion of chondrogenic differentiation media into the depth of TSs, and hence slowed down the chondrogenesis of ADSCs. [22] In addition, since the differentiated chondrocytes in Group 1 aggregated in the form of TSs, it could be assumed that the 3D environment prevented the chondrocytes from dedifferentiation and preserved their chondrogenic phenotype. [35] Due to these appealing properties of TSs made of predifferentiated chondrocytes, Group 1 was preferred for bioprinting experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case 2, cell viability was measured to be ~82%. The decrease in cell viability could be due to the aspiration force or dehydration during the rapid transfer or cell damage when spheroids were submerged into the hydrogel substrate; however, viability levels over 80% for bioprinting of spheroids could still be considered moderate, as viability of fabricated cells aggregates even without bioprinting could be in that range (36). In addition to bioprinting of spheroids, the AAB system also enabled the bioprinting of other biologics.…”
Section: Capabilities Of Aab In Patterning and 3d Bioprinting Of Biolmentioning
confidence: 99%
“…A high degree of cellular compaction, however, may lead to poor oxygen and nutrients diffusion during maturation periods, culminating in loss of cellular viability and function in fibers' core regions. To tackle this challenge, microporous tissue strands were prepared by adding a porogen agent—alginate microbeads—to cellular suspensions before extrusion inside a hollow alginate tube (Figure D) . Fibers comprising adipose‐derived MSCs (ASCs) generated by this methodology showcased approximately 25% porosity and high pore interconnectivity.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%